FEATURES OF USING METHODS AND FORMS OF THE TEACHING ORGANIZATION IN A SMALL SCHOOL (2ND HALF OF 20TH CENTURY) AND THEIR IMPROVEMENT IN MODERN CONDITIONS - Prokopiv, Liubov (Mountain School of Ukrainian Carpaty, 2018)
This article is about methods and forms of organization of training in a small school. The problem is actualized in the context of the adopted strategy for modernizing general secondary education, namely the Concept of the New Ukrainian School, in accordance with which the restructuring of the educational sector is being carried out in the rural areas as well. The purpose of the article is to identify features of using methods and forms of teaching organization in a small school (2nd half of the 20th century) and effective methods and forms of teaching organization at the present stage. The article has the following tasks: to describe the methods of teaching organization in a small school in accordance with the selected stages; to specify the basic forms of teaching organization in small schools of the studied period; to identify the effective aspects of implementing the partnership pedagogy in the Carpathian educational space. In order tosolve the research tasks, the following theoretical methods were used: analysis and systematization of psychological, pedagogical and methodical literature; analysis of archival, sources sociological surveys, questionnaires and interviews The author conducted questionnaires, surveys and interviews confirmed the effectiveness of the innovative teaching methods selected for implementation in the operation of a small school.